On the utility of a mechanistic approach to physiology - descriptive vs. mechanistic biology - Torday, John S. (Henry Stewart Talks, 2016)
History of descriptive physiology, Systems biology, The biota expansion, Downward causation vs. cell-cell signaling, Holism vs. Reductionism: philosophical views about nature, Molecular changes mediating evolution, Cell communication as mechanism of novelty, From phylogeny-ontogeny to homeostasis & repair, Homeostasis as the mechanism for evolution, Explicate/Implicate order